Prehistory in Permafrost: Investigations at the Saqqaq Site, Qeqertasussuk, Disco Bay, West Greenland - Grønnow, Bjarne (Journal of Danish Archaeology, 1988)
Prehistory in Permafrost: Investigations at the Saqqaq Site, Qeqertasussuk, Disco Bay, West Greenland